Cancer-protective effects of inhaled corticosteroids in COPD are likely related to modification of epithelial activation. Issue 3 (12th September 2019) - Soltani, Amir; Mahmood, Malik Q.; Reid, David W.; Walters, E. Haydn
The article published by Raymakers et al . [1] presents a lung cancer-protective effect of inhaled corticosteroids (ICS) in patients with COPD. The authors suggest that this effect is due to "anti-inflammatory" properties of ICS on the airways. This may be partly true but, from what we have come to know of COPD pathogenesis, the situation is likely to be more nuanced and complicated than that. COPD is an independent risk factor for lung cancer. Studies have suggested that inhaled corticostroids have reduced the incidence of lung cancer in these patients. This effect is likely related to modification of epithelial–mesenchymal transition (EMT). http://bit.ly/2Km4VK4